The Influence Of Green Marketing and Green Brand Image nn Green Satisfaction Starbucks Yogyakarta - Yoga Pranata; Sri Rejeki Ekasasi (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2022)
This study aims to find out the impact of green marketing and green brand image on consumers’ green satisfaction Starbucks Yogyakarta. This research method uses a quantitative method assisted by the analysis of SPSS for windows 25. The sampling technique used is a non-probability sampling method with a purposive sampling method with 100 consumers of Starbucks Yogyakarta as respondents. The results of this study show that partially there is a significant positive influence between the green marketing variables toward green satisfaction. and a significant positive influence between the green brand image variables on green satisfaction. In addition, there is also a simultaneous influence between green marketing and green brand image on the green satisfaction of Starbucks Yogyakarta consumers.